Mechanochemical synthesis of small organic molecules - Achar, Tapas Kumar; Bose, Anima; Mal, Prasenjit (Beilstein Journal of Organic Chemistry, 2017)
With the growing interest in renewable energy and global warming, it is important to minimize the usage of hazardous chemicals in both academic and industrial research, elimination of waste, and possibly recycle them to obtain better results in greener fashion. The studies under the area of mechanochemistry which cover the grinding chemistry to ball milling, sonication, etc. are certainly of interest to the researchers working on the development of green methodologies. In this review, a collection of examples on recent developments in organic bond formation reactions like carbon–carbon (C–C), carbon–nitrogen (C–N), carbon–oxygen (C–O), carbon–halogen (C–X), etc. is documented. Mechanochemical syntheses of heterocyclic rings, multicomponent reactions and organometallic molecules including their catalytic applications are also highlighted.
Keywords: ball-milling; green chemistry; mechanochemistry; solid-phase synthesis; solvent-free synthesis